Effect of Confinement on the Properties of Sequestered Mixed Polar Solvents: Enzymatic Catalysis in Nonaqueous 1,4-Bis-2-ethylhexylsulfosuccinate Reverse Micelles - Durantini, Andres Matías (2016)
The influence of different glycerol, N,N-dimethylformamide (DMF) and water mixtures encapsulated in 1,4-bis-2-ethylhexylsulfosuccinate (AOT)/n-heptane reverse micelles (RMs) on the enzymatic hydrolysis of 2-naphthyl acetate by α-chymotrypsin is demonstrated. In the case of the mixtures with DMF and protic solvents it has been previously shown, using absorption, emission and dynamic light-scattering techniques, that solvents are segregated inside the polar core of the RMs. Protic solvents anchor to the AOT, whereas DMF locates to the polar core of the aggregate. Thus, DMF not only helps to solubilize the hydrophobic substrate, increasing its effective concentrations but surprisingly, it does not affect the enzyme activity. The importance of ensuring the presence of RMs, encapsulation of the polar solvents and the corrections by substrate partitioning in order to obtain reliable conclusions is highlighted. Moreover, the effect of a constrained environment on solvent–solvent interactions in homogenous media and its impact on the use of RMs as nanoreactors is stressed.